Mechanism of dielectric barrier discharge plasma technology to improve the quantity of short-chain fatty acids in anaerobic fermentation of waste active sludge - Wang, Jie; Liu, Xingguo; He, Jinling; Cheng, Guofeng; Xu, Junli; Lu, Ming; Shangguan, Yuyi; Zhang, Ai (Frontiers in Microbiology, 2022)
The mechanism of improving the anaerobic fermentation performance of waste active sludge by using dielectric barrier discharge (DBD) plasma pretreatment technology was investigated. The maximum accumulation of short chain fatty acids (SCFAs) was observed on 7th day of anaerobic fermentation when the DBD power was 76.50 W, which was 1726.70 mg COD/L, 1.50 times of the control group. The ratio of acetic acid in DBD group was 9.30% higher than that in control. Further mechanism research indicated that DBD pretreatment can destroy the structure of extracellular polymer substances and release organic substances such as protein and polysaccharide. The dissolved organic matter analysis indicated that DBD technique could increase the release of biodegradable organics (eg., tyrosine proteins, soluble microbial by-products), thus accelerate the biotransformation of organic substance. Bacterial community structure analysis showed that the increase in the abundance of Firmicutes and Bacteroidetes and the decrease in the abundance of Proteobacteria in DBD group were beneficial to the accumulation of SCFAs. Besides, further archaeal analysis indicated that the decrease of Methanosaeta sp. and Methanosarcina sp. abundance in DBD group facilitate acetic acid accumulation. This study demonstrated that DBD technique can be used as an effective and potential pretreatment method to improve sludge anaerobic fermentation performance.